Phonics activities for reading success - Bernstein, Rosella (Center for Applied Research in Education, 1997)
This unique resource provides 60 teaching/ learning units created to help special needs students learn short and long vowels, irregular vowel combinations, diphthongs, and r-controlled vowel sounds.